2000
DOI: 10.1097/00043426-200005000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Sequelae in Children Treated for Acute Lymphoblastic Leukemia With Dexamethasone or Prednisone

Abstract: The findings of this preliminary study are consistent with the hypothesis that dexamethasone therapy can increase risk for neurocognitive late effects in children treated for ALL and indicate that further investigation of this question is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
2
6

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(84 citation statements)
references
References 32 publications
4
72
2
6
Order By: Relevance
“…Dexamethasone also may have an affect on neurocognitive development, particularly as it relates to tasks with a memory demand. 8 Furthermore, the cumulative incidence of bony morbidity, especially fractures, was found to be significantly higher in patients receiving dexamethasone compared with those receiving prednisone. 9 Reilly et al examined the effect of postinduction steroid therapy on energy intake, which leads to the excess weight gain observed in children who complete therapy for ALL.…”
Section: Discussionmentioning
confidence: 94%
“…Dexamethasone also may have an affect on neurocognitive development, particularly as it relates to tasks with a memory demand. 8 Furthermore, the cumulative incidence of bony morbidity, especially fractures, was found to be significantly higher in patients receiving dexamethasone compared with those receiving prednisone. 9 Reilly et al examined the effect of postinduction steroid therapy on energy intake, which leads to the excess weight gain observed in children who complete therapy for ALL.…”
Section: Discussionmentioning
confidence: 94%
“…Waber et al compared patients treated on previous ALL regimens that included different corticosteroid preparations. 26 They found greater neurocognitive impairment in the dexamethasone group for memory, reading comprehension, and mathematics. However, the dexamethasone group also had lower participation rates, younger age at diagnosis, higher rates of cranial radiation (70% vs 50% in the prednisone group), and lower educational attainment by the parents.…”
Section: Discussionmentioning
confidence: 96%
“…We have reported that the substitution of dexamethasone for prednisone during remission induction was associated with a high incidence of septic episodes and deaths 25 and that post-remission dexamethasone may be associated with more severe neurocognitive late effects. 26 The Children's Cancer Group recently reported a 9.3% incidence of osteonecrosis in patients treated with both prednisone and dexamethasone, with higher rates noted in patients receiving higher cumulative doses of dexamethasone. 27 The incidence of osteonecrosis was not prospectively collected on Protocol 91-01, although we observed that 16% of patients experienced a fracture.…”
Section: Discussionmentioning
confidence: 99%